(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The study examined the first-person narrative as a spoken approach, using the ideas of Alan Rabatal, to explore different perspectives and uncover the depth of the narrative’s Point of view. Several important findings emerged from the study, including that the thoughts and viewpoints of non-narrating characters in the first-person narrative are similar to those in the objective narrative. Labeling the perspective of the first-person narrator is not solely determined by the character’s inability to comprehend certain experiences, as in the case of an Anonymous narrator. Instead, the first-person narrator is similar to any character who cannot simultaneously perceive events occurring in different locations. The experiences that the character cannot fully grasp in the first-person narrative are not indications of the narrator’s perspective, but rather significant indicators of the author’s Point of view. The depth of the narrative persona’s perspective and other non-narrating characters is generally limited, but it can be extremely limited or occasionally expand almost boundlessly. While the depth of the first-person narrator’s perspective can sometimes approach unlimited, it cannot be completely unrestricted. Conversely, the author benefits from the unlimited depth of perspective, owing to the first-person narrator’s inability to fully comprehend events taking place in multiple locations simultaneously.